Sonai isolate as potential bacteria for fiber sago hydrolysis to monosaccharide - Prima Endang Susilowati; Sarni Marwanti (PKimia FKIP Universitas Halu Oleo, 2012)
Cellulolytic and xylanolytic enzymes play an important role in natural biodegradation processes in which plant lignocellulosic materials are efficiently degraded by microorganisms. Large amount of fiber sago wastes from renewable sago residues are rich sources of cellulose, hemicellulose and lignin. Hemicelluloses wastes bioavailability conversion presupposes the changing of the macromolecular structure by using enzymes and to result free simple compounds (mono-disaccharide). The purposes of this study are isolation bacteria from water collected in the Sonai hot-springs and use bacteria for bioconversion of fiber sago. Bacteria were isolated on cellulose dan xylan agar medium and screened by the cellulolysis dan xylan method. Determining the reducing sugars liberated from cellulose and xylan using dinitrosalicylic acid (DNS) reagent. The results are identification of bacteria from Sonai hot springs showed 13 isolates potential xylanolitic and cellulose. Isolate IIIB-3 showed maximum xylanase and cellulose production. The isolate can hydrolysis fiber sago at condition optimum fermentation 500C, pH 6, shaker rate 175 rpm, 5% substrate, and 18 hours incubation.